DEVELOPMENT OF INNOVATION MANAGEMENT IN UZBEKISTAN IN CONDITIONS OF GLOBAL COMPETITION (Marketing Journal, 2025)
The article examines current trends in the development of innovation management in Uzbekistan under the conditions of global competition. The analysis is based on strategic documents (“Uzbekistan -2030”, “Digital Uzbekistan -2030”), official statistical data and reports of international organizations (WIPO, World Bank, OECD). It is shown that innovation management is becoming an important tool for enhancing the competitiveness of the national economy as well as a key factor of integration into global markets. Special attention is paid to the development of innovation infrastructure (technoparks, IT Park, free economic zones), mechanisms of state support for startups and R&D, as well as issues of human resources and financing. The study concludes on the necessi ty to activate venture capital, expand cooperation between universities and businesses, and integrate innovative projects into international value chains.
Keywords: innovation management; Uzbekistan; global competition; innovation infrastructure; technopark; IT Park; digitalization; startup; venture financing; competitiveness